Chrysophanol attenuates cognitive impairment, neuroinflammation, and oxidative stress by TLR4/NFκB-Nrf2/HO-1 and BDNF/VEGF signaling in stress-intensified PTZ induced epilepsy in mice - Jehan Zeb Khan; Syeda Rida Zainab; Mujeeb Ur Rehman; Muhammad Abid; Fawad Ali Shah; Najeeb Ur Rehman; Muhammad Khalid Tipu (Frontiers Media S.A., 2024)
BackgroundStress is among the most common comorbid conditions with epilepsy and a strong factor in the pathophysiology of seizures. An imbalance in neuronal circuits causes recurrent unprovoked seizures in epilepsy. Dysregulation of BDNF/VEGF expression, oxidative stress, increased levels of neuroinflammatory cytokines, and increased expression of apoptotic genes contribute to the underlying cause of the seizure.ObjectivesChrysophanol, an anthraquinone, has broad-spectrum therapeutic potential. This study evaluated the neuroprotective effect of chrysophanol with underlying pathways in PTZ-induced epilepsy with stress as a comorbid condition.MethodsMale mice were given 35 mg/kg of PTZ every other day to induce seizures. In addition, they were exposed to 120 min of daily restraint stress for 21 days to induce stress. Chrysophanol (0.1, 1, 10 mg/kg) was administered to the mice 30 min before the PTZ in the acute study. The most effective dose (10 mg/kg) was proceeded for the chronic epilepsy model. Following this, various tests were conducted, including behavioral assessments for memory impairment and stress, analysis of antioxidant levels, histopathological and immunohistochemistry examinations, measurement of cortisol levels using ELISA, and gene expression analysis using RT-PCR.ResultsChrysophanol demonstrated a notable decrease in both the intensity and frequency of seizures. Additionally, it effectively boosted the levels of important antioxidants such as GSH, GST, and CAT, while simultaneously reducing the levels of MDA and Nitric oxide. The histopathological analysis also showed improvement in overall morphology and survival of neurons. Chrysophanol treatment effectively showed an increase in the expression of BCL-2, and Nrf-2 with a decrease in BAX expression confirmed by immunohistochemistry. Dysregulation of vascular permeability factor, production of inflammatory cytokines, and apoptotic gene expression was successfully reversed after chrysophanol treatment analyzed through RT-PCR. Cortisol concentration was decreased in treatment groups analyzed through Enzyme-linked immunoassay. Molecular docking of chrysophanol with different proteins declared the binding affinity of the ligands with the target sites of proteins.ConclusionIn conclusion, chrysophanol demonstrated remarkable neuroprotective and antiepileptic effects at a dose of 10 mg/kg in stress-exacerbated PTZ-induced epilepsy following the TLR4/NFκB -Nrf2/HO-1 and BDNF/VEGF pathways.